Reasoning with Inductive Argument Test: A Study of Validity and Reliability - Mehmet Emrah Karadere; Kasým Fatih Yavuz; Ýbrahim Enis Kayran; Yasir Þafak; Bengü Yücens; Erkan Kuru; Mehmet Hakan Türkçapar (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: The aim of our study is to research reliability and validity and to evaluate the usability of Turkish version of Reasoning with Inductive Argument Test (RIAT) in Turkish healty population. Method: 51 healty volunteers who work in Ankara Dýskapi Yildirim Beyazit Research and Training Hospital participated in this study. Reasoning with Inductive Argument Test (RIAT) was translated into Turkish by three clinical good knowledge of English. Participants were given a sociodemographic data form, and RIAT were performed by clinicians. To test the reliability of the Turkish version of RIAT, Cronbach’s alpha coefficient was calculated and the halving method was used for the test. Results: The internal consistency of the Reasoning with Inductive Argument Test (RIAT) items, Cronbach’s alpha internal consistency coefficient measurements of 0.73 was found to be statistically significant. Spearman-Brown coefficient that determines the reliability of the whole test r=0.74 was found. Kurtosis values of all the items was below 1.5 and the percentages in the second evaluation were mainly lower. At the same time, both change in belief between self produced RIAT options and given RIAT options (p=0.02, z=-2296) as well as changes in beliefs between related and unrelated items for Obsessive Compulsive Disorder (OCD) difference (p=0.03, z=-2.199) were significant. Conclusion: The preliminary data obtained from the study of reliability and validity of the scale shows that ‘Reasoning with Inductive Argument Test’ supports reliability and validity in Turkish population. [JCBPR 2013; 2(3.000): 156-161]